Manajemen Nilai Moderasi Beragama dalam Teknologi Pembelajaran - Wathon, A (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2025)
The implementation of religious moderation values in educational technology presents both challenges and opportunities in the digital era. These values are essential for fostering harmony in an increasingly pluralistic learning environment. This study aims to explore strategies for managing religious moderation values within educational technology in educational institutions. The research employs a qualitative approach with a case study method conducted in several faith-based educational institutions. Data were collected through in-depth interviews, observations, and document analysis. The findings reveal that integrating religious moderation values into educational technology can be achieved through value-based curriculum design, teacher training, and the use of educational applications that promote tolerance. Challenges include resistance from certain parties toward technology and a lack of understanding of the concept of religious moderation. The study concludes that managing religious moderation values in educational technology requires the collaboration of all stakeholders to create an inclusive and harmonious learning ecosystem. Recommendations are provided for developing teacher training programs and educational technology platforms that support religious moderation values.